2015
DOI: 10.1128/aem.01895-15
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Seasonal Variations of Synechococcus Assemblage Structures in Estuarine Waters and Coastal Waters of Hong Kong

Abstract: bSeasonal variation in the phylogenetic composition of Synechococcus assemblages in estuarine and coastal waters of Hong Kong was examined through pyrosequencing of the rpoC1 gene. Sixteen samples were collected in 2009 from two stations representing estuarine and ocean-influenced coastal waters, respectively. Synechococcus abundance in coastal waters gradually increased from 3.6 ؋ 10 3 cells ml ؊1 in March, reaching a peak value of 5.7 ؋ 10 5 cells ml ؊1 in July, and then gradually decreased to 9.3 ؋ 10 3 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
75
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(83 citation statements)
references
References 62 publications
8
75
0
Order By: Relevance
“…). These taxa were previously found to be abundant in the Hong Kong estuarine waters (Xia et al ., ), suggesting that they have a high nutrient requirement and are possibly halotolerant, as it is the case for S5.2 (Chen et al ., ; Dufresne et al ., ).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…). These taxa were previously found to be abundant in the Hong Kong estuarine waters (Xia et al ., ), suggesting that they have a high nutrient requirement and are possibly halotolerant, as it is the case for S5.2 (Chen et al ., ; Dufresne et al ., ).…”
Section: Discussionmentioning
confidence: 95%
“…Amplification of the rpoC1 gene sequences was performed as previously described (Mühling et al ., ). The first round of PCR used the primer rpoC1 ‐N5 and the C‐terminal primer rpoC1 ‐C, and the PCR products were used as templates for a second round of PCR with primer rpoC1 −39F (5′‐adaptor A + barcode + GGNATNGTNTGYGAGCGYTG) and rpoC1 −462R (5′‐adaptor B + CGYAGRCFCTTGRTCAGCTT (Mühling et al ., ; Xia et al ., ). PCR products were gel‐purified using the Qiaquick gel purification kit, as described by the manufacturer (Qiagen, Germany).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Some researchers have reported that the abundance and biomass of Synechococcus sp. showed strong seasonal relationships with temperature [28], and this genera provided important sources of organic carbon and nutrients for the summer food web [29]. This is a health concern in some cases, as Synechococcus blooms can produce harmful toxins [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal differences in surface water and stormwater coliform concentrations have been observed by many investigators (e.g., Hunter and McDonald ; Hathaway et al ; Duris et al ; Meals et al ). Such seasonality is undoubtedly a universal pattern for mesophilic organisms in all waterbodies in temperate climates (Giovannoni and Vergin ; Ran et al ; Xia et al ).…”
Section: Discussionmentioning
confidence: 99%